HUMANITY AND SOCIAL PROBLEMS IN THE EXAMPLE OF HARPER LEE'S "TO KILL A MOCKINGBIRD" - Davlatova Shakhnoza Muhammmadiyevna (Modern American Journals, 2025)
This article explores humanity and social issues in Harper Lee’s To Kill a Mockingbird. Focusing on the experiences of Scout and Jem Finch, the study analyzes how moral development, empathy, and social awareness emerge in a racially segregated and socially stratified community. The paper examines the role of key characters, such as Atticus Finch, in teaching moral principles, and highlights how childhood curiosity and experience shape understanding of justice and ethical behavior. By analyzing examples from the text, the study demonstrates how Lee addresses racial prejudice, class distinctions, and the challenges of maintaining integrity in an unjust society.
Keywords: Harper Lee, To Kill a Mockingbird, Humanity, Social issues, Morality, Empathy, Racial prejudice